Mott Transition in the Mass Imbalanced Ionic Hubbard Model at Half Filling - Yen, Nguyen Thi Hai; Anh, Le Duc; Tuan, Hoang Anh; Thang, Nguyen Toan; Huong, Nguyen Thi (Communications in Physics, 2019)
The Mott - Hubbard metal - insulator transition in the half-filled mass imbalanced ionic Hubbard model is investigated using the two-site dynamical mean field theory. We find that for a fixed mass imbalanced parameter r the critical interaction Uc increases when the ionic energy \(Δ\) is increased. In the other hand, for a fixed \(Δ\), \(U_c\) decreases with increasing the mass imbalance. We also show the existence of BI phase in the system for the case \(Δ e 0\), \(U=0\) and calculate the staggered charge density \(n_B − n_A\) as a function of the interaction for different values of the mass imbalance. Our results in the limiting cases (\(r = 1\); \(Δ e 0\) or/and \(Δ = 0\); \(r e 1\)) are in good agreement with those obtained from full dynamical mean field theory.